2012
DOI: 10.2989/17280583.2011.620961
|View full text |Cite
|
Sign up to set email alerts
|

The influence of psychosocial variables on adolescent suicidal ideation

Abstract: A lack of self-esteem, ineffective coping and particular stressors contributed significantly to the vulnerability of adolescents. Future studies should explore a wider range of dispositional factors that influence effective coping and adjustment in addressing adolescent suicidal ideation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Mirkovic et al (2015) also reported that applying emotion-focused coping methods increased levels of suicidal ideation in adolescents. Adolescents who respond to stressors using emotion-focused coping easily develop negative self-evaluation and thus had increased level of suicidal ideation (George & van den Berg, 2012). After controlling protective factors and interactions between risk factors and protective factors, emotion-focused coping was not significantly associated with suicidal ideation, so the role of emotion-focused coping on suicidal ideation needs further exploration.…”
Section: Discussionmentioning
confidence: 98%
“…Mirkovic et al (2015) also reported that applying emotion-focused coping methods increased levels of suicidal ideation in adolescents. Adolescents who respond to stressors using emotion-focused coping easily develop negative self-evaluation and thus had increased level of suicidal ideation (George & van den Berg, 2012). After controlling protective factors and interactions between risk factors and protective factors, emotion-focused coping was not significantly associated with suicidal ideation, so the role of emotion-focused coping on suicidal ideation needs further exploration.…”
Section: Discussionmentioning
confidence: 98%
“…A number of variables related to adolescent romance have been associated with the risk of suicide attempts or completions in adolescents. These include incongruent partnership role-identities [ 30 ], negative sexual experiences [ 31 ] and stressful events including breakups [ 32 ] and relationship disputes [ 33 ]. Nevertheless, the extent to which romantic relationship issues contribute to suicide risk remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors also involve the social environment to which young people are exposed. Specifically, young people who are socially isolated, involved in difficult romantic relationships, or bullied are likely to score higher on suicidality (George & van den Berg, ; Winsper, Lereya, Zanarini, & Wolke, ). Many of these factors are influenced by familial factors in that children who are bullied, for example, are more likely to come from socially isolated and economically vulnerable ethnic or racial minorities.…”
Section: Familial and Social Risk Factorsmentioning
confidence: 99%